2019
DOI: 10.1016/j.heliyon.2019.e01812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of audiovisual technological aids on students' achievement and interest in secondary school biology in Nigeria

Abstract: While Science teaching and learning is changing at an amazing pace in developed countries, same cannot be said of developing countries. Nigeria secondary school classrooms have remained ‘chalk and board’ affair with students seated in rows copying notes. In a developing country such as Nigeria, teachers need sustained support from colleagues at tertiary level who are compliant with the new technologies to help them learn how best to integrate technology into their teaching. In this paper, we describe a study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 3 publications
1
18
0
2
Order By: Relevance
“…Facilities as consideration are reasonable; given the existence of learning support facilities will be able to improve student learning achievement (Ramli & Zain, 2018). This is supported by the results of research conducted by Ibe and Abamuche (2019) who found that the use of audiovisual-based learning media was able to increase students' interest in learning and presenting. Moreover for children of age, the use of technology will make learning more interesting (Baharuddin & Dalle, 2019).…”
Section: Facilities and Infrastructure Factorsmentioning
confidence: 62%
“…Facilities as consideration are reasonable; given the existence of learning support facilities will be able to improve student learning achievement (Ramli & Zain, 2018). This is supported by the results of research conducted by Ibe and Abamuche (2019) who found that the use of audiovisual-based learning media was able to increase students' interest in learning and presenting. Moreover for children of age, the use of technology will make learning more interesting (Baharuddin & Dalle, 2019).…”
Section: Facilities and Infrastructure Factorsmentioning
confidence: 62%
“…English found out that the challenges encountered in using video arise from curriculum design, technical constraints, and video selections. Ibe & Abamuche (2019) stated that one of the benefits of audio-visual technology could affect student achievement and interest. For example, the students in biology learning activities in junior high schools in the country get the results that the group using integrated audio-visual content achieved higher test scores than the group using the integrated audio-visual content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…De maneira que, o uso das tecnologias pode auxiliar na formação científica e tecnológica (AULER, 2007). O uso de imagens constitui hoje parte fundamental das práticas de ensino, razão pela qual pode-se afirmar que existe, em alguma medida, um consenso sobre o fato, das imagens desempenharem importante papel pedagógico no processo de ensino aprendizagem (IBE e ABAMUCHE, 2019;VIDAL e DE REZENDE, 2010 As respostas dos alunos demonstram que o desenvolvimento de aulas integradoras envolvendo a temática recurso natural ocorrem com pouca frequência. Segundo Fazenda (1993), o pensar interdisciplinar parte da premissa de que nenhuma forma de conhecimento é em si mesma racional.…”
Section: Satisfatóriaunclassified